Hospital preparations of ethanol-free furosemide oral solutions: Formulation and stability study - Charles Bavouma Sombie; J E Kéré Guetambaba; Hermine Zimé Diawara; Josias Yaméogo; Salfo Ouédraogo; Jonathan Goole; Rasmané Semdé (Wolters Kluwer Medknow Publications, 2022)
Furosemide is a diuretic frequently used in the therapeutic management of edema associated with cardiac, renal, and hepatic failure and hypertension. However, there are a very low number of pharmaceutical dosage forms containing furosemide that are suitable for children under 6- years old. Therefore, there is a real need to develop hospital preparations, especially in the hospital. Four oral pediatric solutions of furosemide (2 mg/Ml) were formulated. Two of those solutions did not contain ethanol. For each formulation, 12 batches of 1600.0 Ml were prepared and packaged in 250.0 Ml brown glass bottles with polypropylene screw caps. The physicochemical properties (visual appearance, pH, osmolarity, drug content) and microbiological quality of the finished product were determined on the freshly prepared solutions and after 90 days of storage at 30°C/65% RH. The physicochemical and microbiological characteristics of the freshly prepared solutions were within the prescribed specifications. After 90 days of storage at 30°C/65% RH, the solutions containing sucrose and those without ethanol showed a slight decrease in pH and furosemide content of about 2.5%-4.5% (w/w). Despite this slight decrease, the characteristics remained within the prescribed specifications. Based on the stability profile of the ethanol-free solution containing sorbitol, it could be implemented in hospitals for the care of pediatric patients.